Design and Evaluation of Enhanced Mock Circulatory Platform Simulating Cardiovascular Physiology for Medical Palpation Training - Jae-Hak Jeong; Young-Min Kim; Bomi Lee; Junki Hong; Jaeuk Kim; Sam-Yong Woo; Tae-Heon Yang; Yong-Hwa Park (Applied Sciences, 2020)
This study presents a design and evaluation of a mock circulatory platform, which can reproduce blood pressure and its waveforms to provide palpation experience based on the human cardiovascular physiology. To reproduce the human cardiovascular behavior, especially the blood pressure, the proposed platform includes three major modules: heart, artery and reservoir modules. The heart module reproduces source pressure exerted on the whole system with a controlled time-profile. The artery module consists of a resistance valve to adjust the open area of the vessel and a compliance chamber adjusting the wall stiffness of the ascending aorta. The designed platform was cross validated by comparing the theory with a lumped model, i.e., the windkessel model, the measurements from the mock circulatory platform and the real human body data. As a result, the ventricular and aortic pressure waveforms measured from the designed platform were well matched with those of the actual human body. Parametric studies regarding peripheral resistance and aortic compliance were done for the detailed correlation analysis between human cardiovascular physiology and blood pressure. Since the proposed platform is based on the actual cardiovascular physiology, adjusting the structural parameters of the components can reproduce realistic blood pressure waveforms in a controllable manner. This platform is applicable to blood pressure measurement sensor calibration, palpation training, and haptic feedback.